An Improved Estimation of SuperDARN Heppner‐Maynard Boundaries Using AMPERE Data. Issue 5 (16th May 2020) - Fogg, A. R.; Lester, M.; Yeoman, T. K.; Burrell, A. G.; Imber, S. M.; Milan, S. E.; Thomas, E. G.; Sangha, H.; Anderson, B. J.
Abstract: Super Dual Auroral Radar Network (SuperDARN) ionospheric convection maps are a powerful tool for the study of solar wind‐magnetosphere‐ionosphere interactions. SuperDARN data have high temporal (approximately minutes) and spatial (∼45 km) resolution, meaning that the convection can be mapped on fine time scales that show more detail than the large‐scale changes in the pattern. The Heppner‐Maynard boundary (HMB) defines the low‐latitude limit of the convection region, and its identification is an essential component of the standard SuperDARN convection mapping technique. However, the estimation of the latitude of this boundary is dependent on ionospheric scatter availability. Consequentially it is susceptible to nonphysical variations as areas of scatter in different latitude and local time regions appear and disappear, often due to changing propagation conditions. In this paper, the HMB is compared to an independent field‐aligned current data set from the Active Magnetosphere and Planetary Electrodynamics Response Experiment (AMPERE). A linear trend is found between the HMB and the boundary between the AMPERE Region 1 and Region 2 field‐aligned currents in the Northern Hemisphere, at both solar minimum and solar maximum. The use of this trend and the AMPERE current data set to predict the latitude position of the HMB is found to improve the interpretation of the SuperDARN measurements in convection mapping. Key Points: Scale sizes of the Northern Hemisphere convection (SuperDARN HMB) and FAC region (from AMPERE) are estimated for solar minimum and maximum The location of the convection and FAC boundaries have a linear relationship The latitude of the FAC boundary can be used to improve the estimation of the SuperDARN HMB